Is it Possible to Detect a Rotating Spherical Colloidal Particle? - Olivier Emile; Janine Emile (Advanced Photonics Research)
A single micrometer‐size spherical colloid has been set in rotation by transfer of light orbital angular momentum. This particle is floating at an air–water interface. Steady‐state rotational frequencies of the order of one hertz have been observed, depending on the topological charge of the beam and on its power, in agreement with expected values. The detection is performed using the rotational Doppler shift of the diffused light. Two time constants have been evidenced in the rotational velocity dynamics. The first one is related to the friction of the colloid with the fluid (air and water), whereas the other one is principally associated with the wall friction of the air–liquid interface with the container. This measurement technique makes it possible to identify dynamic parameters of the rotational movement of any spherical object, which is usually impossible to detect.